2018
DOI: 10.1002/jcb.27902
|View full text |Cite
|
Sign up to set email alerts
|

E2F1‐mediated MNX1‐AS1‐miR‐218‐5p‐SEC61A1 feedback loop contributes to the progression of colon adenocarcinoma

Abstract: The long noncoding RNA MNX1‐AS1 has been reported to facilitate the progression of glioblastoma and ovarian cancer. Nevertheless, the biological roles and underlying mechanisms of MNX1‐AS1 in colon adenocarcinoma have not been studied until now. In the current study, MNX1‐AS1 was upregulated in colon adenocarcinoma. JASPAR prediction tool showed that E2F1 could bind to the promoter region of MNX1‐AS1. The chromatin immunoprecipitation assay and luciferase reporter assay were used to verify the interactions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…Up to date, an increasing number of evidence demonstrated that miRNAs play important roles in the pathogenesis of COPD [15]. MiR-218-5p, a member of the miR-218 family, has been investigated to be implicated in various human malignancies [16,17]. Recently, emerging evidence suggested that miR-218-5p participated in the pathogenesis of COPD [18], suggesting the regulatory role of miR-218-5p in the progression of COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, an increasing number of evidence demonstrated that miRNAs play important roles in the pathogenesis of COPD [15]. MiR-218-5p, a member of the miR-218 family, has been investigated to be implicated in various human malignancies [16,17]. Recently, emerging evidence suggested that miR-218-5p participated in the pathogenesis of COPD [18], suggesting the regulatory role of miR-218-5p in the progression of COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [36] found that oncogenic KSHV-encoded interferon regulatory factor up-regulates HMGB2 and CMPK1 to promote cell invasion through disrupting the lncRNA-OIP5-AS1-miR-218-5p network. Ye et al [37] also discovered that E2F1-mediated MNX1-AS1-miR-218-5p-SEC61A1 feedback loop invovled in the progression of colon adenocarcinoma. Our results expand the recognition on miR-218-5p and its competitive endogenous RNA in the development and progression of LUSC.…”
Section: Discussionmentioning
confidence: 97%
“…Former study revealed that E2F1 could promote cancer progression through transcriptionally activating some genes [38,39]. Importantly, the transcriptional of E2F1 on lncRNA has been demonstrated in colon cancer [33]. Interestingly, E2F1 was also identified as a transcription factor at LINC00461 promoter through UCSC database.…”
Section: Discussionmentioning
confidence: 99%